Shiftwork and mortality from ischaemic heart disease. Issue 6 (June 1996) - McNamee, R; Binks, K; Jones, S; Faulkner, D; Slovak, A; Cherry, N M
Abstract : OBJECTIVES: To investigate the relation between shift work and death from ischaemic heart disease (IHD). METHODS: A nested case-control approach was used. The cohort comprised male manual workers who joined an industrial company aged 50 years or under between 1 January 1950 and 31 December 1992 and worked there for at least one month. Cases were 467 cohort members who died during the same period aged 75 years or under, with ischaemic heart disease (IHD) (international classification of diseases (ICD) 410-414) coded from the death certificate. For each case a control worker was chosen, who joined the company at the same age and in the same period but who survived the case. Work status (shift work or day work) was assigned to cases for their entire employment and to controls for that part of their employment which preceded the matching case's death. The main source of information was historical personnel records containing pay codes which differed for day work and shift work. Information on weight, height, blood pressure, and smoking from a pre-employment medical was available. RESULTS: Two thirds of subjects had been employed for at least one month as shift workers and there was evidence that they had slightly better health at recruitment than day workers. The odds ratio for shift workers during the period starting 10 years after shift work began, and after adjustment for height, body mass index, blood pressure, smoking, duration of employment, and job status (skilled or unskilled) was 0.90 (90% confidence interval (90% CI): 0.68-1.21). There was no relation between risk of IHD death, and duration of shift work, but there was evidence of a reduced risk when actively employed as a shift worker, together with an increased risk in the first five years after leaving shift work to do day work. CONCLUSIONS: Shift work did not increase the risk of death from ischaemic heart disease in this study. Those workers with poorer cardiovascular health may be under represented in groups with longer shift work experience because of health related selection out of shift work.